PENGENALAN SURVEI DAN SENAM IMUNITAS MANDIRI SEBAGAI INSTRUMEN PENGUATAN IMUNITAS REMAJA - Purwanto, Bambang; Munir, Misbakhul; Putri, Arum Cahyaning (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2023)
Adolescent is a transitional phase of growth and development from the children to be an adult. Physical, sexuality and immunity are altered during this transition adolescent. Adolescent was commonly suffered for illness due to immunity variability. This community development program was aimed to introduce methods of self-immunity survey and exercise as strengthened instrument for adolescent immunity. Student of Junior High School was the primary target as representative of adolescent. The teachers were asked as facilitator to transfer it knowledge to the students. The Government of Pacitan collaborated to encourage this implemented program on Junior High School. The attendances were 90% of 50 individual invitations. More than 90% attendances finished the course until the post test examination. This program increased teacher’s knowledge two-fold higher in score of tests. Teachers was more familiar to adolescent immunity, especially in self-immunity survey and exercise methods. Further, it needs to be continued to strengthen adolescent immunity among Junior High School students.